2006
DOI: 10.1128/jvi.01186-06
|View full text |Cite
|
Sign up to set email alerts
|

Packaging of Brome Mosaic Virus Subgenomic RNA Is Functionally Coupled to Replication-Dependent Transcription and Translation of Coat Protein

Abstract: In Brome mosaic virus (BMV), genomic RNA1 (gB1) and RNA2 (gB2), encoding the replication factors, are packaged into two separate virions, whereas genomic RNA3 (gB3) and its subgenomic coat protein (CP) mRNA (sgB4) are copackaged into a third virion. In vitro assembly assays performed between a series of deletion variants of sgB4 and wild-type (wt) CP subunits demonstrated that packaging of sgB4 is independent of sequences encoding the CP open reading frame. To confirm these observations in vivo and to unravel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
59
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 39 publications
(70 reference statements)
3
59
0
Order By: Relevance
“…5, lane 1). Similar observations were reported previously with nonreplicating or inefficiently replicating BMV RNA3 variants (1,4). By contrast, efficient accumulation and detection of sgB4 in samples complemented with either TLS 200 or UTR 336 suggested that the 3Ј end of the B3⌬TLS progeny was restored, permitting B3 to enter replication.…”
Section: Downloaded Fromsupporting
confidence: 88%
“…5, lane 1). Similar observations were reported previously with nonreplicating or inefficiently replicating BMV RNA3 variants (1,4). By contrast, efficient accumulation and detection of sgB4 in samples complemented with either TLS 200 or UTR 336 suggested that the 3Ј end of the B3⌬TLS progeny was restored, permitting B3 to enter replication.…”
Section: Downloaded Fromsupporting
confidence: 88%
“…More explicitly, CCMV virions purified from infected leaf tissue display a remarkable homogeneity in size and physical appearance: RNA1 (3,171 nt) and RNA2 (2,774 nt) are each packaged independently into Tϭ3 capsids, whereas RNA3 (2,173 nt) and RNA 4 (824 nt) are copackaged into a third virion. It has been shown that in vivo assembly of nucleocapsids in positive-strand RNA viruses pathogenic to humans (32), animals (4,46), and plants (3) is functionally coupled to replication-dependent transcription and translation, i.e., the assembly is mediated by capsid protein that is translated from replication-derived mRNA (5). Consequently, macromolecular interactions, such as the interaction between CP and viral replicase (RNA1 and RNA2 gene products), resulting from commonly shared subcellular localization sites (6), might play an important role, ensuring that only one kind of stable virion population with Tϭ3 symmetry is assembled and maintained.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism by which the CP regulates this balanced distribution of four BMV RNAs into three individual virions is still unknown. More recent studies using experimental systems that are competent to effectively uncouple replication from packaging revealed that efficient packaging of viral RNA is functionally coupled to replication-dependent transcription and translation in FHV and BMV (5,58). However, it is not known whether such functional coupling between replication-dependent transcription and translation requires homologous replicase machinery.…”
mentioning
confidence: 99%